HBV‐specific CD4+ cytotoxic T cells in hepatocellular carcinoma are less cytolytic toward tumor cells and suppress CD8+ T cell‐mediated antitumor immunity. Issue 8 (11th May 2017) - Meng, Fanzhi; Zhen, Shoumei; Song, Bin
Abstract : In East Asia and sub‐Saharan Africa, chronic infection is the main cause of the development of hepatocellular carcinoma, an aggressive cancer with low survival rate. Cytotoxic T cell‐based immunotherapy is a promising treatment strategy. Here, we investigated the possibility of using HBV‐specific CD4 + cytotoxic T cells to eliminate tumor cells. The naturally occurring HBV‐specific cytotoxic CD4 + and CD8 + T cells were identified by HBV peptide pool stimulation. We found that in HBV‐induced hepatocellular carcinoma patients, the HBV‐specific cytotoxic CD4 + T cells and cytotoxic CD8 + T cells were present at similar numbers. But compared to the CD8 + cytotoxic T cells, the CD4 + cytotoxic T cells secreted less cytolytic factors granzyme A (GzmA) and granzyme B (GzmB), and were less effective at eliminating tumor cells. In addition, despite being able to secrete cytolytic factors, CD4 + T cells suppressed the cytotoxicity mediated by CD8 + T cells, even when CD4 + CD25 + regulator T cells were absent. Interestingly, we found that interleukin 10 (IL‐10)‐secreting Tr1 cells were enriched in the cytotoxic CD4 + T cells. Neutralization of IL‐10 abrogated the suppression of CD8 + T cells by CD4 + CD25 − T cells. Neither the frequency nor the absolute number of HBV‐specific CD4 + cytotoxic T cells were correlated with the clinical outcome of advanced stage hepatocellular carcinoma patients. Together, this study demonstrated that in HBV‐related hepatocellular carcinoma, CD4 + T cell‐mediated cytotoxicity was present naturally in the host and had the potential to exert antitumor immunity, but its capacity was limited and was associated with immunoregulatory properties.